2009
DOI: 10.1017/s1049023x00006889
|View full text |Cite
|
Sign up to set email alerts
|

Air-Medical Transport Experience in Emergency Medicine Residencies: Then and Now

Abstract: Objective:The appropriate activation and effective utilization of air-medical transport (AMT) services is an important skill for emergency medicine physicians in the United States.Previous studies have demonstrated variability with regards to emergency medical services (EMS) experience during residency training. This study was designed to evaluate the nature and extent of AMT training of the emergency medicine residency programs in the United States.Methods:An identity-unlinked survey of the program directors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Model curricula and program descriptions have focused primarily on the provision of medical oversight, quality assurance and improvement activities, education of EMS providers, and in‐field observational experiences 2,3,6,8,9 . However, a variety of other more active experiences have also been described, including resident integration as an in‐field provider within a ground or air EMS system and unique experiences within urban, rural, or wilderness environments 7,12–17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Model curricula and program descriptions have focused primarily on the provision of medical oversight, quality assurance and improvement activities, education of EMS providers, and in‐field observational experiences 2,3,6,8,9 . However, a variety of other more active experiences have also been described, including resident integration as an in‐field provider within a ground or air EMS system and unique experiences within urban, rural, or wilderness environments 7,12–17 …”
Section: Discussionmentioning
confidence: 99%
“…The recommended amount and type of hands‐on experience in out‐of‐hospital care is less well defined, with various published recommendations including involvement in air or ground direct patient care activities and involvement in mass gathering activities and as medical directors for EMS agencies 4,7–9,12–14,16–19 . In a survey of U.S. and Canadian residency programs, Ray and Sole 20 identified that a majority (88%) of programs require observation with ground EMS, while working as an EMS provider is required in 28%.…”
Section: Discussionmentioning
confidence: 99%
“…entering fellowship (9,10). Thus, pediatric subspeciality fellows must learn the unique skills required to serve as TMC during fellowship, prior to transitioning to unsupervised practice.…”
mentioning
confidence: 99%
“…The role of TMC during pediatric interfacility transport is often performed by PCCM physicians, but other pediatric subspecialities including emergency medicine and neonatology also serve as TMC (6–8). Unlike adult emergency medicine residents, who uniformly participate in transport, pediatric trainees are unlikely to have significant experience with interfacility transport prior to entering fellowship (9, 10). Thus, pediatric subspeciality fellows must learn the unique skills required to serve as TMC during fellowship, prior to transitioning to unsupervised practice.…”
mentioning
confidence: 99%
“…entering fellowship (9,10). Thus, pediatric subspeciality fellows must learn the unique skills required to serve as TMC during fellowship, prior to transitioning to unsupervised practice.…”
mentioning
confidence: 99%